Domestic Slaughter in Southern Italy, with special reference to Campania Region - Soppelsa, Ottavio; di Martino, Chiara (Ethnobiology and Conservation, 2020)
The relationships between animals and humans date back thousands of years. Cultures around the world developed specific ways of interacting with the fauna over time, so that human communities accumulated a huge deposit of animal knowledge closely integrated with many other anthropological aspects focused on the human-animal relationship. Through the administration of a questionnaire-interview, in this work we studied ritual aspects related to animal slaughter, as well as the link between the slaughterhouse and the time of the year. Moreover, the apotropaic uses of Bos taurus Linnaeus, 1758 and Sus scrofa domesticus Erxleben, 1777, by local rural communities, were analyzed. The data we collected come with important witnesses, supported by old pictures and tools used during the slaughter that reinforced the story of the interviewee, allowing to draw a timeline after which the relationship between man and farm animals moves and gets modified. These almost forgotten rituals constitute an important ethnozoological knowledge to be integrated into our human cultural heritage. To the best of our data, this is the first study documenting the apotropaic uses of Bos taurus Linnaeus, 1758 and Sus scrofa domesticus Erxleben, 1777. All the questionnaires, administered in Campania, were analyzed and compared in the search of ritual customs, archaic beliefs and ancient legacies still present today and inherited from elder times. Rites surrounding animal slaughter aimed at communicating with the divine and at explaining all those processes that cannot be readily answered. Man, by making animals the protagonists of mythological tales and investing them with a sacred force, has linked to the slaughtering act a psychological component that has led the killing itself to being configured as a ritual. From the witnesses gathered, interesting parallelisms emerged stimulating thoughts on a serious and complex dichotomy of our present-day society: a meat-based diet versus the total rejection of it.Integrating scientific knowledge with local ecological ones, the informations collected in this work can be used to design an effective and targeted conservation management strategy for these mammals as valid alternative to intensive farming.